« La vision d’un monde marquée par les pratiques locales » au prisme du roman policier – entre « villes » et « campagnes » - Daisuke Fukunishi (Ebisu: Études Japonaises)
Crime fiction and ethnography have a great deal in common. They originated at the same time, while the regional focus in both fields has shifted over time from the “city” to the “countryside”. Within works of both genres, writers create worlds based on local practices. Additionally, the ethnographic concept of the “marebito” (guest/visitor/outsider) can be found within crime fiction. The problems that arise in the closed space of the countryside are resolved by entities (a deity, a detective) from outside (the beyond, the city). The ethnographic usage of the “marebito” concept was first developed to understand folk traditions. It is from that base that the concept made its way into crime fiction, offering an explanation for the genre’s popularity among the Japanese public. The depiction of regional practices in these works plays an important role in understanding contemporary Japanese society.